I have heard of a land. - Thomas, Joyce Carol ([New York] : HarperCollins Publishers, 1998)
Describes the joys and hardships experienced by an African-American pioneer woman who staked a claim for free land in the Oklahoma territory.
Joanna Cotler books."
All Juvenile
Keywords: Oklahoma--History--Land Rush, 1889--Fiction.; Frontier and pioneer life--Fiction.; African Americans--Fiction.; Oklahoma--History--Land Rush, 1889--Juvenile fiction